Edukasi Program Latihan Keseimbangan Pada Masyarakat Lansia Untuk Menurunkan Risiko Jatuh di Posyandu Pronorogo Lestari Ngamarto RW 7-Lawang - Tri Noor Cahyo Widodo; Novita Lorenza Azahroh; Siti Ainun Ma’rufa; Nadya Setyarini Farizka (Universitas Muhammadiyah Manado, 2023)
As elderly people age, their body's physiological functions will decrease. Decreased dynamic balance in the elderly can cause a high risk of falls. If this is not addressed, the risk of injury to the elderly will be greater. The aim of this research is to provide education and training to the elderly about dynamic balance and the risk of falls and how to do exercises to reduce these symptoms. This research method was carried out using a community service approach at the elderly posyandu by providing counseling material about